Exploring Systems That Support Good Clinical Care in Indigenous Primary Health-care Services: A Retrospective Analysis of Longitudinal Systems Assessment Tool Data from High-Improving Services - Woods, Cindy; Carlisle, Karen; Larkins, Sarah; Thompson, Sandra Claire; Tsey, Komla; Matthews, Veronica; Bailie, Ross (Frontiers in Public Health, 2017)
Background Continuous Quality Improvement is a process for raising the quality of primary health care (PHC) across Indigenous PHC services. In addition to clinical auditing using plan, do, study, and act cycles, engaging staff in a process of reflecting on systems to support quality care is vital. The One21seventy Systems Assessment Tool (SAT) supports staff to assess systems performance in terms of five key components. This study examines quantitative and qualitative SAT data from five high-improving Indigenous PHC services in northern Australia to understand the systems used to support quality care. Methods High-improving services selected for the study were determined by calculating quality of care indices for Indigenous health services participating in the Audit and Best Practice in Chronic Disease National Research Partnership. Services that reported continuing high improvement in quality of care delivered across two or more audit tools in three or more audits were selected for the study. Precollected SAT data (from annual team SAT meetings) are presented longitudinally using radar plots for quantitative scores for each component, and content analysis is used to describe strengths and weaknesses of performance in each systems’ component. Results High-improving services were able to demonstrate strong processes for assessing system performance and consistent improvement in systems to support quality care across components. Key strengths in the quality support systems included adequate and orientated workforce, appropriate health system supports, and engagement with other organizations and community, while the weaknesses included lack of service infrastructure, recruitment, retention, and support for staff and additional costs. Qualitative data revealed clear voices from health service staff expressing concerns with performance, and subsequent SAT data provided evidence of changes made to address concerns. Conclusion Learning from the processes and strengths of high-improving services may be useful as we work with services striving to improve the quality of care provided in other areas.